Enhancement of Surface-Enhanced Raman Spectroscopy for Bacterial Characterization Using Functionalized Silver Nanoparticles - Khan, Jahangir; Hafiz Misbah Ud Din,; Rehmat, Ali; Farhana,; Alam, Hafiz Munsif; Razaq, Rabeea; Batool, Aysha; Saleem, Sadia; Ahmed, Umair; Siddiqi, Muhammad Arslan (Indus Journal of Bioscience Research, 2025)
Surface-enhanced Raman Spectroscopy (SERS) has gained considerable interest as an effective method for bacterial detection owing to its exceptional sensitivity and ability to identify bacterial species at minimal concentrations. Using silver nanoparticles (AgNPs) to improve Raman signals has demonstrated significant potential for advancing bacterial characterization in clinical and environmental contexts. Nonetheless, challenges persist in enhancing SERS for intricate microbial settings such as biofilms and heterogeneous bacterial communities. This study aimed to examine the effect of functionalized AgNPs on augmenting SERS for bacterial detection, emphasizing strengthening the method's sensitivity and selectivity for bacterial identification in intricate microbiological samples. This laboratory experiment used AgNPs functionalized with biomolecular ligands to amplify the Raman signal of several bacterial strains, including Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa, and Streptococcus pneumoniae. The study conducted at University of Agriculture Faisalabad, Punjab, Pakistan. The study also used SERS spectroscopy to quantify the signal enhancement. At the same time, statistical methods, including One-Way ANOVA and Tukey's HSD test, were employed to investigate the differences in SERS intensities between bacterial strains with and without AgNPs. The findings indicated that functionalized AgNPs markedly improved the SERS signal intensity across all tested bacterial strains, yielding a 30% augmentation in Raman signal intensity. The SERS enhancement factor varied among the bacterial strains. S. aureus showed the highest enhancement factor, but the difference across strains is quite small, suggesting similar levels of enhancement. Statistical analysis validated that the augmented SERS signals were substantial (p < 0.05), and the AgNP functionalization facilitated enhanced bacterial detection sensitivity. These data indicate that AgNP-based SERS is an effective strategy for bacterial detection, offering enhanced sensitivity and selectivity for identifying bacterial pathogens in complicated environments. The research emphasizes the potential of employing functionalized silver nanoparticles to enhance fast microbial detection in clinical and environmental contexts.